ANALYSIS OF THE ROLE OF BSI GLOBAL ISLAMIC FINANCE SUMMIT (GIFS 2025) IN DRIVING INDONESIA'S ECONOMIC GROWTH THROUGH SHARIA FINANCIAL ECOSYSTEM STRENGTHENING - Siti Nur Rohma; Ainun Fadillah; Riki Gunawan; Nurul Hikmah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
BSI Global Islamic Finance Summit (GIFS) 2025 is a strategic initiative by Bank Syariah Indonesia (BSI) to strengthen Indonesia's position as a major player in the global sharia-based economy. This study analyzes the contribution of GIFS 2025 in driving Indonesia's economic growth by strengthening the sharia financial ecosystem, with a focus on financial inclusion, halal investment, and utilization of the real sector. The research method used is qualitative analysis based on literature studies and relevant secondary data. The results of the study show that GIFS 2025 plays an important role in increasing collaboration between industry players, government, and global investors, which in turn accelerates the development of the sharia financial sector in Indonesia. This forum is also the main catalyst in facilitating financing for the real sector and MSMEs, as well as increasing the competitiveness of the Indonesian economy in the global market. This study recommends policy strategies to maximize the positive impact of GIFS on national economic growth.